(x-y)/4+(x+y)/5=1/4 (x+y)/9-(x-y)/3=//2
化简[(3x+4y)^2-(2x+y)(2x-y)+(-x+y)(5x-y)]除以-2y,其中x=-1,y=1
已知x=1/3,y=-1/2,求代数式x-(x+y)+(x+2y)-(x+3y)+(x+4y)-(x+5y)+...-(
{4/(x+y)+6/(x-y)=3 {9/(x-y)-1/(x+y)=1
{3(x+y)-4(x-y)=4 {x+y/2 + x-y/6=1
已知4x=9y求(1)x+y/y (2)y-x/2x
3(x+y)-4(x-y)=11,2(x-y)+5(x+y)=27
9y=3x-(x-1),4(x+y)-(2x+4)=8y
先化简再求值(x-y)(x+y)-(x-2y) 的完全平方+x(3x-5y)-(x-y)(x-2y),其中x=1/2 y
数学题……555{(3x+y)(3x-y)-(x-5y)(5x-y)-(x-2y)²÷(-4x),x=-2.y
已知x²+y²+5=2x+4y,求【2x²-(x-y)(x-y)】【(x+y-1)(x-y
3x-2y=1 4x-5y
(4x-2y-z)-{5x[8y-2y-(x+y)]-x+(3y-10z)]=? kuai